2008
DOI: 10.1016/j.neuro.2008.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Manganese accumulates primarily in nuclei of cultured brain cells

Abstract: Manganese (Mn) is known to pass across the blood-brain barrier and interact with dopaminergic neurons. However, the knowledge on the subcellular distribution of Mn in these cell types upon exposure to Mn remained incomplete. This study was designed to investigate the subcellular distribution of Mn in blood-brain barrier endothelial RBE4 cells, blood-cerebrospinal fluid barrier choroidal epithelial Z310 cells, mesencephalic dopaminergic neuronal N27 cells, and pheochromocytoma dopaminergic PC12 cells. The cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…Recent studies have linked Mn-induced changes in T 1 relaxation rates (DR 1 ) to intracellular Mn content in rat brain, and have found a linear correlation between R 1 and Mn concentrations obtained from tissue homogenates (36,37). These data, however, cannot be applied to the present study to extrapolate Mn concentrations, as different cell types have been found to sequester intracellular Mn very differently (38). In brain cells, Mn preferentially accumulates in the nuclei.…”
Section: Effect Of Mn On Nmr Parameters In Isolated Islets Under Perfmentioning
confidence: 82%
“…Recent studies have linked Mn-induced changes in T 1 relaxation rates (DR 1 ) to intracellular Mn content in rat brain, and have found a linear correlation between R 1 and Mn concentrations obtained from tissue homogenates (36,37). These data, however, cannot be applied to the present study to extrapolate Mn concentrations, as different cell types have been found to sequester intracellular Mn very differently (38). In brain cells, Mn preferentially accumulates in the nuclei.…”
Section: Effect Of Mn On Nmr Parameters In Isolated Islets Under Perfmentioning
confidence: 82%
“…b p < 0.01. Article to occur (13). Using the direct chemical imaging nano-SXRF method, we evidenced that Mn is located principally within the Golgi apparatus of PC12 cells cultured in normal conditions, without adding Mn to the culture medium ( Figure 3).…”
Section: Discussion Manganese Subcellular Localization and Toxicitymentioning
confidence: 99%
“…It is generally accepted that Mn accumulates within the mitochondria of neuronal cells (11,12). However, a recent report suggests that less than 0.5% of intracellular Mn is found in the mitochondrial fraction and that Mn rather accumulates into the nucleus and cytoplasm of PC12 cells (13).…”
mentioning
confidence: 99%
“…It is also unclear how the manganese causes neural damage. Some studies have found that the metal accumulates in high concentrations within the mitochondria of glial cells and that symptoms may be the result of disrupted energy metabolism [101], but data in this arena remain discordant [39,57].…”
Section: Pathogenesismentioning
confidence: 99%